Virulence potential of filamentous fungi isolated from poultry barns in Cascavel, Paraná, Brazil - Cleison Ledesma Taira; Nadir Rodrigues Marcondes; Valdeci Aparecido Mota; Terezinha Inez Estivalet Svidzinski (Universidade de São Paulo, 2011)
Opportunistic fungi are those that normally would not cause diseases in otherwise healthy people, but are able to cause problems under some circumstances, and for this they need to possess a certain virulence potential. The objective of this study was to identify samples of filamentous fungi isolated from poultry barns in Cascavel, Paraná, and also to evaluate their virulence potential by assessing proteinase production, hemolytic activity, urease production, and growth rate at 37 ºC. We have evaluated the following samples: Acremonium hyalinulum (1 sample), Aspergillus sp. (12), Beauveria bassiana (1), Curvularia brachyspora (1), Paecilomyces variotti (1), and Penicillium sp. (2). Out of the 18 samples analyzed, 44.4% showed proteolytic activity using albumin as the substrate versus 66.7% when using casein; 66.7% showed hemolytic activity, 83.3% were positive for urea, and 88.9% grew at a temperature of 37 ºC. The results demonstrated that the majority of the isolates expressed virulence factors. Therefore, these isolates have the potential to harm human hosts, such as those working at poultry barns, especially predisposed or susceptible individuals. Fungos oportunistas são aqueles que normalmente não causariam doenças em pessoas saudáveis, mas eles são capazes de causar problemas sob certas circunstâncias e, para isso, eles necessitam possuir algum potencial de virulência. O objetivo deste trabalho foi identificar amostras de fungos filamentosos isolados de granjas de aves em Cascavel, Paraná, e também avaliar o seu potencial de virulência, verificando a produção de proteinase, atividade hemolítica, produção de urease e crescimento a 37 ºC. Foram avaliados Acremonium hyalinulum (01), Aspergillus sp (12), Beauveria bassiana (01), Curvularia brachyspora (01), Paecylomices variotti (01) e Penicillium sp (02). Das 18 amostras, 44,4% apresentaram atividade proteolítica usando como substrato a albumina e 66,7% com caseína; 66,7% demonstraram atividade hemolítica, 83,3% foram uréia positivas e 88,9% cresceram em temperatura de 37 ºC. Os resultados demonstram que a maioria dos isolados expressaram fatores de virulência e, portanto, têm potencial para causar danos a hospedeiros humanos como os trabalhadores dos aviários, sobretudo em indivíduos predispostos ou suscetíveis.